Assessing the Effects of Rearing Environment, Natural Selection, and Developmental Stage on the Emergence of a Behavioral Syndrome. (15th March 2013) - Sweeney, Kayla; Gadd, Ryan D. H.; Hess, Zachary L.; McDermott, Donna R.; MacDonald, Leigh; Cotter, Patrick; Armagost, Fawn; Chen, Jason Z.; Berning, Aric W.; DiRienzo, Nicholas; Pruitt, Jonathan N.; Koenig, W.
Abstract Although there is much interest in behavioral syndromes, very little is known about how syndromes are generated in wild populations. Here, we assess the roles of correlated selection and divergent rearing environments in generating a syndrome between foraging aggressiveness and boldness in the spider Agelenopsis pennsylvanica. We first tested for and confirmed the presence of a behavioral syndrome between boldness and foraging aggressiveness in wild penultimate A. pennsylvanica (r = 0.24). Then, to assess the effects of rearing environment on the boldness–aggressiveness syndrome, we compared the behavioral tendencies of field‐ vs. laboratory‐reared spiders over the course of their development. The presence of the boldness–aggressiveness syndrome differed based on spiders' developmental stage and rearing environment: field‐reared juveniles did not exhibit a syndrome between boldness and foraging aggressiveness, but field‐reared penultimates did. In contrast, laboratory‐reared spiders never exhibited a behavioral syndrome, regardless of their developmental stage. Thus, the boldness–aggressiveness syndrome in A. pennsylvanica manifests only when individuals are reared in the field. Selection data from a mark–recapture study failed to indicate any signature of correlated selection, despite our finding that at least one element of the syndrome (foraging aggressiveness) can respond to selection (Heritability h2 = 0.27, from mid‐parent breeding study). Thus, contemporary correlated selection does not appear to be a major driver of the boldness–aggressiveness syndrome of A. pennsylvanica. Taken together, our data are consistent with the hypothesis that the boldness–aggressiveness syndrome exhibited by wild A. pennsylvanica develops as a result of environmentally induced phenotypic plasticity, and not correlated selection.